Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1039/d2nr06330a
|View full text |Cite
|
Sign up to set email alerts
|

Orientation order of a nonpolar molecular fluid compressed into a nanosmall space

Abstract: The ordering structures of non-polar carbon tetrachloride liquid compressed to nano-scales between parallel substrates is studied in this work. The theoretical considerations show that the potential well formed by the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…However, in most studies, the layering property is also found to be critical when the number of confined particles increases to a certain value. 32–34 For example, Wang et al applied MD simulations to investigate the adsorption of hydrocarbons in nanoscale pores of unconventional systems, which revealed that multiple layers of the adsorbed gas phase and liquid phase hydrocarbons exist in the confined pore space. 9 In this case, as the particle density inside the confined space is very high and the confined space is very small, layer formation is regulated by the interaction between the particle and the surface, as well as the entropy, which may lead to several layered structures.…”
Section: Resultsmentioning
confidence: 99%
“…However, in most studies, the layering property is also found to be critical when the number of confined particles increases to a certain value. 32–34 For example, Wang et al applied MD simulations to investigate the adsorption of hydrocarbons in nanoscale pores of unconventional systems, which revealed that multiple layers of the adsorbed gas phase and liquid phase hydrocarbons exist in the confined pore space. 9 In this case, as the particle density inside the confined space is very high and the confined space is very small, layer formation is regulated by the interaction between the particle and the surface, as well as the entropy, which may lead to several layered structures.…”
Section: Resultsmentioning
confidence: 99%